A new species of Phanerotoma Wesmael (Hymenoptera: Braconidae: Cheloninae) from the Andaman Islands, India - Gupta, Ankita; Achterberg, Cornelis Van (Zootaxa, 2014)
A new species Phanerotoma andamanensis Gupta & van Achterberg sp. nov. is described from the Andaman Islands, India. Differences of the new species from the other Oriental species are discussed. Phanerotoma agarwali Varshney & Shujauddin, 1999, is a junior synonym of P. syleptae Zettel, 1990, syn. nov.